Respuesta :

Answer:

18x + 6 = 2( 9x + 3 )

18x + 6 = 3( 6x + 2 )

18x + 6 = 6( 3x + 1 )

Step-by-step explanation:

Answer:

1. 2(9x+3)

2. 3(6x+2)

3. 6(3x+1)

Step-by-step explanation:

Okay so in the first one there is a 2 outside of the parentheses which means we will multiply whatever is inside of the parentheses by 2.

9x*2=18x

3*2=6

18x+6=2(9x+6)

Okay so in the second one there is a 3 outside of the parentheses which means we will multiply whatever is onside of the parentheses by 3.

6x*3=18x

2*3=6

18x+6=3(6x+2)

Okay so in the third one there is a 6 outside of the parentheses which means we will multiply whatever is inside of the parentheses by 6.

3x*6=18x

1*6=6

18x+6=6(3x=1)